2022
DOI: 10.1111/1750-3841.16309
|View full text |Cite
|
Sign up to set email alerts
|

Effect of drying method on the production of in vitro short‐chain fatty acids and histone deacetylase mediation of cocoa pod husk

Abstract: We evaluated the effect of cocoa pod husk (CPH) processing (microwave [MW], forced-air drying [FAD], and FAD plus extrusion [FAD-E]), and in vitro gastrointestinal digestion on the in vitro human colonic fermentation metabolism, in vitro bioactivity on human HT-29 colon cancer cell, and the in silico mechanism of selected compounds. CPH as a substrate for human colonic microbiota significantly decrease local pH (MW −0.7, FAD −0.2, and FAD-E −0.3, 24 h) and modifies their metabolic activity (short-chain fatty a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…Among the bioactive compounds with the greatest presence are theobromine (764 to 9028 mg/kg), caffeine (150 to 3370 mg/kg), epicatechin (4 to 748 mg/kg), catechin (12 to 180 mg/kg), and other minor compounds such as procyanidin type A and type B [6] . In the CPH of CCN51 genotype, around 111 mg/g of phenolic compounds have been found, and the antioxidant activity using the ABTS radical was 155 µmol of Trolox equivalent per grams of sample [3] .Recently, in an in silico study, it has been reported that epicatechin and catechin from CPH are highly associated with the inhibitory activity of histone deacetylase 6 in HT-29 colorectal cancer cells [7] , and epicatechin has also been shown to promote the inhibition of fibroblast growth factor receptor 3 (FGFR3) gene signalling pathways by inducing changes in elongation primary cilium of chondrocytes and promote femur lengthening [8] .…”
Section: Introductionmentioning
confidence: 99%
“…Among the bioactive compounds with the greatest presence are theobromine (764 to 9028 mg/kg), caffeine (150 to 3370 mg/kg), epicatechin (4 to 748 mg/kg), catechin (12 to 180 mg/kg), and other minor compounds such as procyanidin type A and type B [6] . In the CPH of CCN51 genotype, around 111 mg/g of phenolic compounds have been found, and the antioxidant activity using the ABTS radical was 155 µmol of Trolox equivalent per grams of sample [3] .Recently, in an in silico study, it has been reported that epicatechin and catechin from CPH are highly associated with the inhibitory activity of histone deacetylase 6 in HT-29 colorectal cancer cells [7] , and epicatechin has also been shown to promote the inhibition of fibroblast growth factor receptor 3 (FGFR3) gene signalling pathways by inducing changes in elongation primary cilium of chondrocytes and promote femur lengthening [8] .…”
Section: Introductionmentioning
confidence: 99%